Aloimunização eritrocitária em pacientes com doença falciforme do Estado do Amazonas - Lins, Pollyana Acordi Cabete (2017)
Sickle cell disease (DF) is now one of the main inherited diseases, with global distribution, being its therapy the prevention of complications and clinical treatment erythrocyte alloimmunization in patients with falciform disease of the state of Amazonas. With the use of transfusion therapy of red blood cells, patients have a large blood transfusion history, resulting in several complications. Among them, the most important is erythrocyte alloimmunization. Different mechanisms have been presented to understand the development of this adverse reaction between responders and no responders ranging from antigenic characteristics to immunological aspects of the patient, as well as the number of transfusions and the presence of co infections at the moment of transfusion. Objective: We developed this study for the investigation of erythrocyte alloimmunization in patients with FD accompanied by the State of Amazonas. Materials and Methods: We studied sickle cell patients attended in which the clinical and laboratory findings were evaluated regarding the number of transfusions and the impact on the presence of irregular antibody. Results: A total of 163 patients were studied, of which 27(16,56%) had single or multiple alloantibodies, generally directed against 12 antigens, most notably anti-E (28.2%), anti-Kell (23.0%), 4 patients RhD Positive with anti-RhD (10.2%) and anti-Dia of the Diego system (10.2%), regarding the number of transfusion was observed a higher frequency of alloimmunization in the patients with the highest number of transfusion. Conclusion: In view of the presented results, it is possible to infer the importance of the implementation of an extended phenotype program of donors and polytransferred patients considering regional characteristics and that transfusion therapy may be related to the process of aloimmunization with the formation of autoantibodies suggesting an immunomodulation reaction, these results being of great value in clinical and laboratory orientation, in order to promote safety in transfusion therapy